Sex differences and testosterone interfere with the structure of the gut microbiota through the bile acid signaling pathway - Duan, Xueqing; Nie, Yinli; Xie, Xin; Zhang, Qi; Zhu, Chen; Zhu, Han; Chen, Rui; Xu, Jun; Zhang, Jinqiang; Yang, Changfu; Yu, Qi; Cai, Kun; et al. (Frontiers in Microbiology, 2024)
The gut microbiome has a significant impact on human wellness, contributing to the emergence and progression of a range of health issues including inflammatory and autoimmune conditions, metabolic disorders, cardiovascular problems, and psychiatric disorders. Notably, clinical observations have revealed that these illnesses can display differences in incidence and presentation between genders. The present study aimed to evaluate whether the composition of gut microbiota is associated with sex-specific differences and to elucidate the mechanism.16S-rRNA-sequencing technology, hormone analysis, gut microbiota transplantation, gonadectomy, and hormone treatment were employed to investigate the correlation between the gut microbiome and sex or sex hormones. Meanwhile, genes and proteins involved bile acid signaling pathway were analyzed both in the liver and ileum tissues.The composition and diversity of the microbiota from the jejunum and feces and the level of sex hormones in the serum differed between the sexes in young and middle-aged Sprague Dawley (SD) rats. However, no similar phenomenon was found in geriatric rats. Interestingly, whether in young, middle-aged, or old rats, the composition of the microbiota and bacterial diversity differed between the jejunum and feces in rats. Gut microbiota transplantation, gonadectomy, and hormone replacement also suggested that hormones, particularly testosterone (T), influenced the composition of the gut microbiota in rats. Meanwhile, the mRNA and protein level of genes involved bile acid signaling pathway (specifically SHP, FXR, CYP7A1, and ASBT) exhibited gender-specific differences, and T may play a significant role in mediating the expression of this pathway.Sex-specific differences in the structure of the gut microbiota are mediated by T through the bile acid signaling pathway, pointing to potential targets for disease prevention and management techniques by indicating that sex differences and T levels may alter the composition of the gut microbiota via the bile acid signaling pathway.